Exponentially Fitted Local Discontinuous Galerkin Method for Convection-Diffusion Problems (Journal of Computational Mathematics, 2012)
In this paper, we study the local discontinuous Galerkin (LDG) method for one-dimensional singularly perturbed convection-diffusion problems by an exponentially fitted technique. We prove that the method is uniformly first-order convergent in the energy norm with respect to the small diffusion parameter.